The maritime security is a powerful tool for resolving a coastal state dispute: it provides a secure and safe systematic guideline. - Shah Md. Omer Farque Jubaer1; Syed Hasan Shahriar Rofi; Shuvrangshu Roy; Md. Atiqur Rahman Numan (Peerian Journals Publishing, 2022)
In essence, this research paper looks at how security concerns have shaped the formation of the law of the sea, as well as how same interests are currently influencing how the law of the sea is interpreted and applied. In view of the shifting dynamics of exclusive and inclusive claims to ocean use, it contends that security interests should be given more weight in our understanding of the law of the sea. Security interests in the oceans have traditionally been linked to different governments' military interests, and this component remains important in inter-state interactions as well as internal state military priorities decision-making. While the safeguarding of sovereignty and national interests remains paramount in maritime security, there is growing recognition of a shared interest among states in responding to a variety of maritime security concerns. The grounds for addressing this topic reflect a deeper understanding and fear of maritime security, especially the possible impact of terrorist attacks on global trade if the maritime industry is targeted. A variety of legal initiatives have been launched in order to improve maritime security onboard ships, in ports, and at sea.
Keywords: initiatives; launched; improve; security